Are sharia firms able to mitigate the involvement of institutional ownership on earnings management? - Adiwijaya, Zainal Alim; Hanafi, Rustam (LPPM ISNJ Bengkalis, 2025)
Purpose - This study examines Shariah firms' role in mitigating institutional ownership's involvement in earnings management. Method - The sample uses a purposive sampling method for firms listed on the IDX from 2015 to 2021. This study analyzes 2,238 firm-year observations using multiple linear regression analysis, multigroup regression, and independent t-tests. The results of this study support research that argues that institutional ownership positively affects earnings management. This study also proves that Sharia firms have lower earnings management than non-Sharia firms, but Sharia firms cannot mitigate the involvement of institutional ownership in earnings management. Findings - These results have practical implications for regulators and investors. For regulators, the findings highlight the importance of developing policies that strengthen oversight of institutional investors to minimize earnings manipulation. For investors, understanding the role of institutional ownership in earnings management can aid in making informed investment decisions and assessing financial statement reliability. Implications - Theoretical implications of this study indicate that companies adhering to Sharia compliance norms can reduce agency problems. Furthermore, these findings reinforce social norms and institutional theory, suggesting that ethical and religious factors (Sharia compliance) serve as internal control mechanisms against opportunistic managerial behavior.